Pengaruh Metode Discovery Terhadap Kemampuan Menggambar Ilustrasi Kartun Karya Siswa Kelas VIII SMP Negeri 1 Pegajahan - Nadya Nadya; Sugito Sugito (Mahesa Research Center, 2022)
This study aims to determine whether there is an effect of the discovery method on the ability to draw cartoon illustrations. The objects drawn are cartoon illustrations using conventional methods and discovery methods by guided discovery learning, namely by providing an illustrated image module that has been designed in such away. The population in this study were all students of class VIII Pegajahan 1st Junior High School with a total sample of 224 students and the sample taken was class VIII-6, amounting to 32 students taken by cluster random sampling technique. The research method used is quasi-experimental research with a randomized control group pretest-posttest design. The research findings show that there is a significant positive effect from the application of the discovery method on the ability to draw cartoon illustrations of class VIII students of Pegajahan 1st Junior High School, as evidenced by tcount = 2.55 and ttable for degrees of freedom = (n₁ + n₂)-2 = 62 at the level of significance (α) = 0.05 is ttable = 1.9989, it turns out that tcount > ttable (2.55 > 1.9989). The big influence of the discovery method on the ability to draw cartoon illustrations is 3.79% or equivalent to 4%.